Teaching, sharing experience, and innovation in cultural transmission. Issue 1 (6th July 2022) - Tilston, Ottilie; Bangerter, Adrian; Tylén, Kristian
Abstract: Teaching is widely understood to have an important role in cultural transmission. But cultural transmission experiments typically do not document or analyse what happens during teaching. Here, we examine the content of teaching during skill transmission under two conditions: in the presence of the artefact (no-displacement condition) and in the absence of the artefact (displacement condition). Participants built baskets from various materials to carry as much rice as possible before teaching the next participant in line. The efficacy of baskets increased over generations in both conditions, and higher performing baskets were more frequently copied; however, the weight of rice transported did not differ between conditions. Displacement affected the choice of strategy by increasing innovation. Teachers shared personal experience more to discuss non-routine events (those departing from expectations) than they did other types of teaching, especially in the presence of the artefact. Exposure to non-routine experience sharing during teaching increased subsequent innovation, supporting the idea that sharing experience through activities such as storytelling serves a sensemaking function in teaching. This study thus provides experimental evidence that sharing experience is a useful teaching method in the context of manual skill transmission.